DETERMINATION OF REAERATION COEFFICIENT K2 FOR POLLUTED STREAM AS A FUNCTION OF DEPTH, HYDRUALIC RADIUS, TEMPERATURE AND VELOCITY (Nigerian Journal of Technology, 2012)
A polluted stream was studied to determine the effect of geometric parameters like velocity, depth, Hydraulic radius and temperature on water quality and its modeling. The data from  sample stations include velocity of flow, average depth of flow, DO, self purification ratio (f) and reaeration constant (K2). The reaeration coefficient ranged from 0.01d-1 to 0.19d-1. Three new empirical models for K21, K22 and K23 were derived from field data by multiple regression analysis. The coefficient of correlation between K2 observed and K21 predicted; K22 derived from hydraulic radius and  K23 predicted from model constructed with effect of Temperature are 0.789, 0.808 and  0.914 respectively. The predictions indicated  significant relationship with the observed values at 95% level of significance.